Let the Record Show - Practical Uses for Historical Documents - Coate, Charles (Teaching History: A Journal of Methods, 1991)
How could historical records help the Dance Theatre of Harlem, a fourth grade class, a botanist, and homeowners lobbying for a new bridge? This fast moving videotape shows us that "these people needed information from the past" and concludes, "It may be hard to foresee now, but at some time historical records are sure to be useful to you too."